Predicting Switching Intention Among Generation Y Using DeLone & McLean (Study on Shopee App) - Made Pradnyan Permana Usadi; Putu Wahyu Dwinata JS; I Putu Oka Permadi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2022)
The objective of this study is to look at the impact of systemquality, information quality, and service quality on satisfaction and switchingintention among Generation Y Shopee users. Data analyzed using PartialLeast Square. The result shows that system quality, information quality, andservice quality significantly has a positive impact on satisfaction. At thatpoint satifaction was moreover found to have a negative impact on intentionto switch. Service quality was found to have a more prominent impact. Thisimplies that Shopee needs to focus on improving service quality, since serviceis considered to have an important part in determining user satisfaction.